CONSTELLATION AND VERNACULARIZATION OF JAVANESE TEXTURE OF THE QUR’AN: CHARACTERISTICS AND CULTURAL LOCALITY OF JAVANESE PONDOK PESANTREN IN TAFSIR AL-IBRĪZ LI MA’RIFAH TAFSĪR AL-QUR’AN AL-AZĪZ - Dewi, Ajeng Indira (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2023)
The existence of the Qur’an as a holy book that is salih li kulli zaman wa makan is relevant to the complexity of traditions and societal problems that are experiencing development and change, which more or less influence the diversity of understanding of the Qur’an. Like the spread of Islam to Indonesia, it has implications for the emergence of many products of Qur’an interpretation, and a product of interpretation cannot be separated from space and time. Like the book of Tafsir Al-Ibriz, it is a form of response and reception from Bisri Musthafa for reading the text of the Qur’an, a dialectic between text, context, and interpreter. The book of Tafsir Al-Ibriz has a strong locality. Supported by Bisri Musthafa’s excellence as the book's author, he also has his own added values, such as the ability to articulate, documentation, organizing which have implications for his product interpretations. This research is a type of library research supported by descriptive analytic interpretation. Based on the study results, it was concluded that the contents of the book Tafsir Al-Ibriz were written over four years using a textual-contextual approach (more dominant textual). This interpretation has several features, including fiqhi, sufi, and adabi ijtima’i. His interpretation is coloured by the life in which he lives, namely the pesantren environment, as well as his scientific journey for two years in Mecca, as well as a socio-religious organization in which he is active as one of the administrators and initiators of his qanun asasi, namely Nahdhatul Ulama.